Melatonin and prolonged physical activity attenuated the detrimental effects of diabetic condition on murine cardiac tissue. (April 2021) - Rahbarghazi, Afshin; Siahkouhian, Marefat; Rahbarghazi, Reza; Ahmadi, Mahdi; Bolboli, Lotfali; Mahdipour, Mahdi; Haghighi, Leila; Hassanpour, Mehdi; Sokouti Nasimi, Fatemeh; Keyhanmanesh, Rana
Graphical abstract: Highlights: The combination of exercise and melatonin could increase antioxidant capacity in the mouse model of diabetes mellitus. Melatonin plus exercise could reduce the apoptotic changes in diabetic cardiomyocytes. Histopathological changes were reduced in the cardiac tissues by the combination of melatonin and exercise. Microvascular density was increased in the diabetic myocardium after mice received melatonin and subjected to exercise. Abstract: In this study, the combined effects of four-week swimming training and melatonin were examined on the oxidative response, inflammation, apoptosis, and angiogenesis capacity of cardiac tissue in the mouse model of diabetes. The mice were randomly allocated into five groups (n = 10 per group) as follows: Control; Diabetic group; Diabetic + Melatonin group; Diabetic + Exercise group; and Diabetic + Exercise + Melatonin group. 50 mg/kg streptozotocin was intraperitoneally administrated. In melatonin-treated groups, melatonin was injected intraperitoneally at 3 mg/kg body weight for four weeks and twice weekly. Swimming exercises were performed for four weeks. We measured cardiac superoxide dismutase, glutathione peroxidase enzymes, malondialdehyde, and total antioxidant capacity. The expression of tumor necrosis factor-α, Caspase‑3, Sirtuin1, and Connexin-43 was measured using real-time PCR analysis. The vascular density was analyzed by immunohistochemistry using CD31 and α-smooth muscle actin antibodies. The combination of melatonin and exercise elevated cardiac superoxide dismutase, glutathione peroxidase coincided with the reduction of malondialdehyde and increase of total antioxidant capacity as compared to the diabetic mice (p < 0.05). In Diabetic + Exercise + Melatonin mice, tumor necrosis factor-α, Caspase‑3 was significantly down-regulated compared to the Diabetic group (p < 0.05). Melatonin and exercise suppressed the expression of Connexin-43 and Sirtuin1 in diabetic mice in comparison with the control mice (p < 0.05). H & E staining showed necrosis and focal hyperemia reduction in the Diabetic + Exercise + Melatonin group compared to the Diabetic group. Data showed a decrease of CD31 + and α-smooth muscle actin + vessels in the Diabetic group as compared to the normal samples (p < 0.05). The number of CD31 + vessels, but not α-smooth muscle actin + type, increased in the Diabetic + Exercise + Melatonin group compared to the Diabetic mice. These data demonstrated that exercise along with melatonin administration could diminish the detrimental effects of diabetes on cardiac tissue via using different mechanisms.